(untitled) («СОВРЕМЕННЫЕ ФИЛОЛОГИЧЕСКИЕ ПАРАДИГМЫ: ВЗАИМОДЕЙСТВИЕ ТРАДИЦИЙ И ИННОВАЦИЙ», 2025)
As an literary trend originated from the nomadic cultures, the images of animals inevitably play an important part in Prairie Literature. In the works of Prairie Literature, the animals are not seen as the appendants of human, instead, they are seen as equals as human beings, with their own distinct characteristics and wisdom, and sometimes nobler spirits compared with human beings. The images of animals in the Prairie Literature reflects the attitudes towards animals and nature of the nomadic culture and break the “human-nature” duality. In the works of Chingiz Aytmatov and Zhang Chengzhi, animals often serve as the alter egos of the main characters, which, is another common feature of the Prairie Literature.